L’ usage des fragments arabes (Le Caire, Taymūr Pāšā 290 aḫlāq) dans l’ édition arabo-latine de la Summa Alexandrinorum - Woerther, Frédérique (Oriens, 2020)
Résumé Following the work of Dunlop (1974) and Badawī (1979), this study aims to prepare the way for a new edition of the Arabic fragments of the Iḫtiṣār al-Iskandarāniyyīn , which are preserved in Cairo manuscript Taymūr Pāšā 290 aḫlāq . This second phase of the project concerns a precise comparison between these Arabic fragments and the corresponding passages in the Arabo-Latin translation of the Summa Alexandrinorum , which was completed by Hermann the German in 1243 and will soon be published in a new edition. Comparing the Arabic fragments with the corresponding passages in Latin makes it possible: 1) to enhance earlier attempts to compile a glossary of Arabic and Latin terms as used by Hermann in his translations; 2) to evaluate how these Arabic fragments can properly be used for the new edition of the Arabo-Latin version of the Summa Alexandrinorum ; 3) to draw some conclusions about the status of these Arabic fragments and Hermann’s methods, as well as Hermann’s underlying aims. The paper concludes by offering a methodological perspective on the forthcoming edition of the Summa Alexandrinorum in its Arabo-Latin version.